Analisis Kinerja Jaringan Irigasi Berdasarkan Faktor Teknis Dan Non Teknis Di Jaringan Irigasi Bener Kecamatan Kejayan Pasuruan - Pahalawan, Rudi; Maulidiyah, Afrikhatul (Tolis Ilmiah : Jurnal Penelitian, 2025)
This study aims to analyze the performance of the Bener Irrigation Network in Kejayan District, Pasuruan Regency, based on technical and non technical factors to support sustainable food security. The evaluation was conducted using a descriptive approach with a mixed quantitative and qualitative method, including field observations, channel condition measurements, and questionnaires distributed to 30 P3A farmer members and 5 irrigation management officers. Technical factors were assessed through the physical condition of primary and secondary channels, while non technical factors included community participation, maintenance budget availability, and institutional coordination. The results indicate that the primary channels have an average condition value of 78.88% (moderate category), while the secondary channels have an average of 70.08% (moderate category) with a higher level of damage. Non technical factors are the main challenge, characterized by low farmer participation, limited maintenance funding, and uneven water availability throughout the year. Questionnaire results revealed that although 100% of respondents acknowledge the existence of P3A and consider it active, only 49% believe the infrastructure functions sustainably, and most stated that irrigation water is not always available year round. Overall, the performance of the Bener Irrigation Network is considered fairly good but requires improvement through channel rehabilitation, institutional strengthening, and participatory management strategies to achieve sustainable irrigation performance.